2018
DOI: 10.1002/pros.23660
|View full text |Cite
|
Sign up to set email alerts
|

Sustained influence of infections on prostate‐specific antigen concentration: An analysis of changes over 10 years of follow‐up

Abstract: While PSA has been previously shown to rise during acute infection, these findings demonstrate that PSA remains elevated over a longer period. Additionally, the overall infection burden, rather than solely genitourinary-specific infection burden, contributed to these long-term changes, possibly implying a role for the cumulative burden of infections in prostate cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Viewing our findings in the context of the longer‐term or cumulative influences of current and/or resolved infections rather than the acute influences of infection, our nonsignificant findings are consistent with those from previous cross‐sectional studies of nonlifelong infections ( T. vaginalis and syphilis) that observed null associations with PSA, but differ from those from other cross‐sectional and longitudinal studies that observed positive findings for C. trachomatis serostatus and histories of medical record–confirmed chlamydia and NCNGU diagnoses with PSA concentration and trajectories in younger men . However, in the latter study, positive associations were observed only when PSA trajectories were examined and not when only one PSA measurement was used (% with PSA ≥0.7 ng/mL = 38.3 for chlamydia, 39.6 for gonorrhea, and 31.7 for NCNGU vs 37.1 for controls without these infections; P = 0.772, 0.639, and 0.659, respectively). This latter finding is more in line with our findings and suggests that smaller long‐term changes may require longitudinal measurements rather than one cross‐sectional measurement to detect as statistically significant.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Viewing our findings in the context of the longer‐term or cumulative influences of current and/or resolved infections rather than the acute influences of infection, our nonsignificant findings are consistent with those from previous cross‐sectional studies of nonlifelong infections ( T. vaginalis and syphilis) that observed null associations with PSA, but differ from those from other cross‐sectional and longitudinal studies that observed positive findings for C. trachomatis serostatus and histories of medical record–confirmed chlamydia and NCNGU diagnoses with PSA concentration and trajectories in younger men . However, in the latter study, positive associations were observed only when PSA trajectories were examined and not when only one PSA measurement was used (% with PSA ≥0.7 ng/mL = 38.3 for chlamydia, 39.6 for gonorrhea, and 31.7 for NCNGU vs 37.1 for controls without these infections; P = 0.772, 0.639, and 0.659, respectively). This latter finding is more in line with our findings and suggests that smaller long‐term changes may require longitudinal measurements rather than one cross‐sectional measurement to detect as statistically significant.…”
Section: Discussionsupporting
confidence: 87%
“…For the present study, we selected a random sample of 750 men with stored specimens in the DoDSR who met the following criteria: were less than 25 years old as of 1995, were HIV‐1 negative, had served on continuous active duty from 1995‐2006, and had multiple serum specimens archived within the repository, including one from 2004‐2006 . We used these criteria to ensure comparability with our broader parent study of STIs and PSA . For each of these men, we selected the most recent serum specimen collected from 2004‐2006.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As chlamydial infections are the most prevalent sexually transmitted disease, as expected, the majority (n= 20) of the articles dealt with Chlamydia trachomatis or related pathogens, followed by Neisseria gonorrhoeae (n = 7), Mycoplasma spp. While most of the articles discuss the general effects of sexually transmitted male genital tract infections, only five articles [10][11][12][13][14] dealt with the long-lasting effects of the infection. Three of these articles discussed chlamydial infections [12][13][14] and two various viruses [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…While most of the articles discuss the general effects of sexually transmitted male genital tract infections, only five articles [10][11][12][13][14] dealt with the long-lasting effects of the infection. Three of these articles discussed chlamydial infections [12][13][14] and two various viruses [10,11]. In the male, depending on the pathogen, the health issues reported ranged from chronic prostatitis, vesiculitis or epididymo-orchitis, leading to hormonal imbalances and testicular dysfunction, with disturbed spermatogenesis eventually resulting in temporary or permanent infertility.…”
Section: Resultsmentioning
confidence: 99%